Nutrition for swimming - Burke, L. M. (World book of swimming: From science to performance, 2012)
The nutritional concerns of swimmers involve an amalgam of challenges. During the training phase, swimmers share the priorities of endurance athletes, whereas issues in the competition setting are more related to brief duration events. Swimmers often begin a competitive career at a young age, adding their sports nutrition needs to the dietary challenge of adolescence and early adulthood. Achieving the ideal physique is a key challenge for many swimmers. Issues include meeting the high energy needs for growth and training in young male swimmers, adapting energy intake to the reduced energy requirements of the taper or off-season, or dealing with the gain of body fat in female swimmers as they progress through puberty. Strategie eating around key workouts and races is important to enhance training outcomes and competition performance. Swimmers are fascinated by the array of sports foods and supplements that promise improved performances. Among the many products on the market, a few offer legitimate benefits -either helping the swimmer meet their daily nutritional goals (e.g. sports drinks, liquid meal supplements, and sports bars), or by directly enhancing performance and recovery (e.g. creatine, bicarbonate, caffeine). The decision to use such products needs to be balanced against the expense and the risk that they may cause an inadvertent doping outcome.